Coming to terms with social media monitoring: Uptake and early assessment. (December 2015) - Trottier, Daniel
Police and other investigative agencies face new challenges and opportunities with the growth of social media platforms. They can now access several categories of technologies that monitor social media and analyse their content. Social media monitoring is being trialled in a global context, and European Union member states in particular are contemplating the extent to which police should adapt to these investigative technologies. This exploratory research draws on a series of interviews to identify the grounds for establishment, set-up and on-going investment costs, and amount of staff required for social media monitoring. It also considers how technological affordances like automated data processing and interoperability are tempered by localised institutional and legal contexts.